2020
DOI: 10.3390/app10124204
|View full text |Cite
|
Sign up to set email alerts
|

Quality Monitoring for Micro Resistance Spot Welding with Class-Imbalanced Data Based on Anomaly Detection

Abstract: Micro resistance spot welding (MRSW) is an important technology widely used in electronics manufacturing for micro component joining. For the joining of micro enameled wire, quality control is heavily dependent on manual inspection till now. In this paper, a quality monitoring approach based on isolation forest (iForest) is proposed to identify abnormal welds and normal welds. Electrode voltage and welding current of over 110,000 spot welds were collected from a production line. The dynamic resistance and heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In comparison to conventional denoising techniques such as the Statistical Outlier Removal (SOR) filter and the Radius filter, the proposed method stands out with an impressive 30% enhancement in denoising accuracy, especially for noise points located near tree trunks. Zeng et al [27] focuses on the application of isolation forest (iForest) in quality monitoring for micro resistance spot welding (MRSW) used in electronics manufacturing, particularly for joining micro enameled wires. The iForest-based anomaly detection model effectively distinguishes incomplete fusion welds from normal ones and can enhance online quality monitoring in enameled wire welding processes in production.…”
Section: Isolation Forest Outlier Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to conventional denoising techniques such as the Statistical Outlier Removal (SOR) filter and the Radius filter, the proposed method stands out with an impressive 30% enhancement in denoising accuracy, especially for noise points located near tree trunks. Zeng et al [27] focuses on the application of isolation forest (iForest) in quality monitoring for micro resistance spot welding (MRSW) used in electronics manufacturing, particularly for joining micro enameled wires. The iForest-based anomaly detection model effectively distinguishes incomplete fusion welds from normal ones and can enhance online quality monitoring in enameled wire welding processes in production.…”
Section: Isolation Forest Outlier Detectionmentioning
confidence: 99%
“…Yet, machine learning algorithms frequently encounter challenges such as outliers and imbalanced datasets, which can reduce accuracy. Research has demonstrated that addressing these issues by applying the Isolation Forest (iForest) method to remove outliers [23][24][25][26][27] and utilizing Adaptive Synthetic Sampling (ADASYN) for balancing imbalanced data [28][29][30][31][32][33][34][35] can lead to improved predictive system performance.…”
Section: Introductionmentioning
confidence: 99%